Cardiovascular risks associated with low-dose ibuprofen and diclofenac as used OTC. (February 2014) - Moore, Nicholas; Salvo, Francesco; Duong, Mai; Blin, Patrick; Pariente, Antoine
Abstract : Introduction: The cardiovascular (CV) risks of non-steroidal anti-inflammatory drugs (NSAIDs) are dose- and duration-dependent. As over-the-counter (OTC) NSAIDs are widely used for the treatment of common painful disorders, without medical supervision, their cardiovascular risks need to be assessed. Areas covered: Individual clinical trials and observational studies of the CV risks associated with NSAIDs and meta-analyses thereof were retrieved and analysed. The article focuses on the risk associated with low-dose ibuprofen and diclofenac, two drugs available OTC in many countries. Very few studies reported on dose-related CV risks of NSAIDs. The usual cut-off for low-dose ibuprofen was 1200 mg daily, the upper limit of the approved OTC daily dose. For diclofenac, the usual cut-off was 100 mg, 33% above the approved daily dose for OTC preparations (75 mg/day). Only one study reported on the CV risks of doses at or below this limit. The studies retrieved found a clear dose-dependent risk with both drugs and no clearly increased cardiovascular risk for doses at or below the maximal approved OTC doses. No study looked at actual OTC usage. Expert opinion: At doses below the maximal daily OTC dose and for durations associated with OTC usage, there was no clear association with increased CV risk.